(3JdNjU GdeaJGM aj GdeYGfj hGdHjGfs - (3GdbRhjfj GdOeTbj, CHh GdeYGdj, GdNWjH (B- (3LdGd GdOjf, eMeO Hf YeQ Hf YHO GdQMef, (B739 (3g`s ((3YHO Gddg Hf HTjQ GdHhSJhjs)
(3ChdgG (B:s
(3fGfGbU GdChd, hChdg(B: (3hLhg BNQ JhQK GdcdGe MSfG haj GdeJcde edcI jbJOQ HgG Ydi JCdja cdGe HdjZs
(3BNQgG (B:s
(3hgPG OYGA ddHQjI TGed hLejY ahGJM GdShQ hNhGJjegG hGQOI Ydi CMSf GdhLhg hCcedgG jXgQ Pdc HGdJCed eY GdJPcQ deG JbOes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 192s
(3eYLe GdeDdajf(B: 3 / 396s
(3cTa GdXfhf(B: 1 / 473s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs